Richard Jones's Tamburlaine the Great, or How to Print an Early Modern Play and Sequel - Baricz, Carla (The sixteenth century journal, 2020)
The Lord Admiral's Men performed Christopher Marlowe's 1 Tamburlaine and its sequel, 2 Tamburlaine, sometime around 1587. When the printer Richard Jones published the two plays together in 1590, however, he resorted to a collected edition and labeled the two plays a "discourse" "divided" into "two parts." He ignored the plays' performance history and published 1 and 2 Tamburlaine as though together they formed a single dramatic entity. He moreover changed the play's genre, made a number of cuts, added paratextual material, and chose an octavo format. This article argues that Jones published the plays in a collected, two-part edition hoping that, by doing so, he would increase the prestige of the works. By publishing Marlowe's plays as though Marlowe were an established author, Jones hoped that he could make him one. The essay suggests that it is Jones's Tamburlaine, rather than Marlowe's, that we read and perform today.